2007
DOI: 10.1300/j137v15n02_12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Familial Factors and Psychopathology on Suicidality Among African American Adolescents

Abstract: SUMMARYRacial differences in familial factors, psychopathology, perceptions of social support, and socioeconomic status were examined in a matched sample of African American and White suicidal adolescents (N = 90) during a psychiatric hospitalization. Exploratory analyses suggest that significant differences were found in family support and its association with psychopathology, but most noteworthy were the many similarities between the two adolescent groups. The results presented in this study represent new kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Multi‐racial adolescents experienced more negative social and emotional outcomes, including having ‘seriously considered suicide’ than those from mono‐racial backgrounds. Outcomes were worse for multi‐racial adolescents where it was the mother who was from the minority group, although a smaller, clinical study did not reflect these findings (Joe et al ., ). A study of 226 Latina adolescents echoed an earlier finding that familialism reduced family conflict, enhanced self‐esteem and was protective against suicide attempts (Kuhlberg et al ., ).…”
Section: Child Characteristicsmentioning
confidence: 97%
“…Multi‐racial adolescents experienced more negative social and emotional outcomes, including having ‘seriously considered suicide’ than those from mono‐racial backgrounds. Outcomes were worse for multi‐racial adolescents where it was the mother who was from the minority group, although a smaller, clinical study did not reflect these findings (Joe et al ., ). A study of 226 Latina adolescents echoed an earlier finding that familialism reduced family conflict, enhanced self‐esteem and was protective against suicide attempts (Kuhlberg et al ., ).…”
Section: Child Characteristicsmentioning
confidence: 97%
“…Toward this end, it remains less clear whether the oft‐cited associations in epidemiological and cross‐sectional studies can be replicated in samples comprising Black American adolescents (Beck, Steer, & Brown, ; Fitzpatrick et al., ; Goldsmith, ; Joe et al., ; Shain, ). Some studies have shown greater rates of suicide behavior in Black American adolescents than their White American counterparts (Greening & Stoppelbien, ), whereas other studies have shown lower or similar rates of suicide behavior among Black American adolescents compared to White American adolescents (Joe, Clarke, Ivey, Kerr, & King, ; Merchant et al., ; Nock et al., 2013; Saluja et al., ).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Based on cross‐sectional and epidemiological studies, substance use and abuse disorders have been posited as a serious risk factor for suicide completion in all populations, including adolescents (APA, ; Joe et al., ). Alcohol and drug use have often been linked with increased odds of suicide attempts and completions in both adult and youth samples (Aseltine, Schilling, James, Glanovsky, & Jacobs, ).…”
Section: Brief Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A fourth limitation is that many important factors evidenced in the literature were not included in the current investigation (see Suicide Prevention Resource Center & Rodgers, 2011). For example, a family history of suicide attempts, mental health disorders, racism, discrimination, religion, racial identity, impulsivity, hopelessness, and family cohesion may also explain and predict suicide ideations and behaviors in Black American adolescents (Brent et al, 2009;Goldston et al, 2008;Joe et al, 2007;O'Donnell et al, 2004;Perkins & Hartless, 2002).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%